2019
DOI: 10.1371/journal.pone.0212571
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin regulation of ankyrin-repeat and SOCS-box protein 9 (ASB9) in ovarian follicles and identification of binding partners

Abstract: Ankyrin-repeat and SOCS-box protein 9 (ASB9) is a member of the large SOCS-box containing proteins family and acts as the specific substrate recognition component of E3 ubiquitin ligases in the process of ubiquitination and proteasomal degradation. We previously identified ASB9 as a differentially expressed gene in granulosa cells (GC) of bovine ovulatory follicles. This study aimed to further investigate ASB9 mRNA and protein regulation, identify binding partners in GC of bovine ovulatory follicles, and study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 66 publications
2
16
0
Order By: Relevance
“…The studied ASB proteins, ASB5 and ASB11, display very strong evolutionary conservation of their primary structure with each other and with ASB9 ( Tables S6 and S7 ; [ 38 ]). These proteins have been implicated in regulating the size of the SkM and brain component (ASB5), gastrointestinal expansion and regenerative and embryonic myogenesis (zebrafish asb9/11), and spermatogenesis and ovarian granulosa cell maturation (ASB9) [ 38 , 52 ]. Unlike the evidence for the role of asb9/asb11 in myogenesis in zebrafish, ASB9 and ASB11 genes exhibited negligible expression in human Mb and Mt ( Table S5c ).…”
Section: Resultsmentioning
confidence: 99%
“…The studied ASB proteins, ASB5 and ASB11, display very strong evolutionary conservation of their primary structure with each other and with ASB9 ( Tables S6 and S7 ; [ 38 ]). These proteins have been implicated in regulating the size of the SkM and brain component (ASB5), gastrointestinal expansion and regenerative and embryonic myogenesis (zebrafish asb9/11), and spermatogenesis and ovarian granulosa cell maturation (ASB9) [ 38 , 52 ]. Unlike the evidence for the role of asb9/asb11 in myogenesis in zebrafish, ASB9 and ASB11 genes exhibited negligible expression in human Mb and Mt ( Table S5c ).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the results suggest that these receptors would activate different targets upon cytokines binding and they could play significant roles in signaling pathways controlling either granulosa cells (GC) proliferation and function, ovulation or formation of the CL. We have previously shown that the expression of several genes was dramatically reduced in the ovulatory follicle following the LH surge or hCG injection [30] , [31] . Cytokines whose receptors are induced by LH/hCG, such as the pro-inflammatory cytokine IL15 shown in this study, may be involved in various biological processes such as the ovulation process but could also hinder GC proliferation and follicular growth.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have established that the LH surge positively regulates genes involved in inflammation, cellular movement, tissue remodeling, and angiogenesis, while switching off the expression of genes involved in metabolism and proliferation in multiple species (D. T. Liu et al, 2017; Wissing et al, 2014). The transcription of specific genes that control the growth of a bovine DF is therefore rapidly downregulated or silenced in granulosa cells (GC) as a result of LH‐mediated increases in intracellular signaling while LH/human chorionic gonadotropin (hCG) upregulates or induces the expression of genes involved in ovulation and luteinization as shown in different species including rodents or in the bovine species (Benoit et al, 2019; Christenson et al, 2013; Espey & Richards, 2002; Gilbert et al, 2011; Li et al, 2009; Lussier et al, 2017). We previously identified genes induced in GC of bovine ovulatory follicles following hCG and including Ankyrin‐repeat and SOCS‐box protein 9 (ASB9) (Lussier et al, 2017).…”
Section: Introductionmentioning
confidence: 99%